Membraneless organelles-based integrative analysis constructs an immune-related prognostic signature and identifies NRG1 as a novel methylation biomarker in colorectal cancer - Cheng, Jingsong; Chen, Nanting; Yin, Qingyao; Zheng, Ziheng; Chen, Xue; Zhu, Xinyi; Wan, Yuanyuan; Wang, Ningxi; Luo, Siqi; Zhang, Chengxi; Liu, Guodong; Chen, Weilong; et al. (Frontiers in Immunology, 2025)
BackgroundThe dysfunction of membraneless organelles (MLOs) has been implicated in tumorigenesis and progression by aberrant liquid–liquid phase separation (LLPS). However, the role of MLOs in the prognosis and tumor immune microenvironment (TIME) of colorectal cancer (CRC) remains unclear.MethodWe integrated transcriptomic data of MLO-related genes to identify distinct CRC subtypes and constructed a prognostic risk score termed MPRS. Then, we systematically demonstrated the characteristics of MPRS based on multi-omics analyses. We further assessed NRG1’s LLPS possibility, prognostic significance, and its correlation with methylation through comprehensive analysis and in vitro experiment.ResultsA prognostic signature called MPRS associated with prognosis, tumor ecotypes, genomic alterations, TIME patterns, immunotherapy responses, chemotherapy sensitivity in CRC patients. NRG1, identified as the most important MPRS gene with high predicted LLPS propensity—was significantly downregulated in CRC tissues and correlated with prognosis. Promoter methylation was found to be a crucial mechanism underlying NRG1 downregulation, which could be rescued by 5-Aza-2-deoxycytidine (Aza) treatment. The qRT-PCR, IHC and Aza treatment were utilized for in vitro validation.ConclusionOur integrated multi-omics analysis constructed the MPRS model to delineate CRC tumor ecology and identified NRG1 as a methylation biomarker with predicted phase-separation propensity, with potential therapeutic implications that warrant prospective validation.